Berberine protects diabetic nephropathy by suppressing epithelial-to-mesenchymal transition involving the inactivation of the NLRP3 inflammasome. Issue 1 (31st December 2022) - Ma, Zejun; Zhu, Lili; Wang, Shangshang; Guo, Xin; Sun, Bei; Wang, Qilong; Chen, Liming
Abstract: Accumulating evidence has implicated that berberine (BBR) has a beneficial effect on diabetic kidney disease (DKD), but its mechanism is not clear. The aim of this study was to assess whether berberine could alleviate tubulointerstitial fibrosis and attenuate epithelial-to-mesenchymal transition (EMT) and its possible molecular mechanism. High-fat diet (HFD) followed by injection of STZ was used to induce diabetic rats in vivo . After the onset of diabetes, rats were treated with either BBR or saline for 12 weeks. In vitro, the human renal proximal tubular epithelial cell line (HK-2) was exposed to high glucose, with or without BBR. The influence of berberine on renal tubulointerstitial histological changes, markers of epithelial-to-mesenchymal transition (EMT) and (NOD-like receptor pyrin domain-containing protein 3) NLRP3 inflammasome expression were examined. Results showed that in vivo, BBR could significantly ameliorate microalbumin and renal pathologic changes in diabetic rats. Immunofluorescence showed that BBR could inhibit EMT. Furthermore, BBR could down-regulate the level of the NLRP3 inflammasome in diabetic rats. Consistently, in vitro, BBR suppressed high glucose-induced EMT and activation of NLRP3 inflammasome in HK-2. Our study demonstrated that BBR could inhibit high glucose-induced EMT and renal interstitial fibrosis by suppressing the NLRP3 inflammasome. BBR might be used as a novel drug to ameliorate tubulointerstitial fibrosis in DKD.